Accelerated large volume irradiation with Dynamic Jaw: dynamic couch helical tomotherapy - Krause, Sonja; Beck, Sebastian; Schubert, Kai; Lissner, Steffen; Herfarth, Klaus; Debus, Jürgen; Sterzing, Florian (Radiation oncology, 2012)
Helical Tomotherapy (HT) has unique capacities for the radiotherapy of large and complicated target volumes. Next generation Dynamic Jaw/Dynamic Couch HT delivery promises faster treatments and reduced exposure of organs at risk due to a reduced dose penumbra.